Augmenting the potency of third-line antibiotics with Berberis aristata: In vitro synergistic activity against carbapenem-resistant Escherichia coli. (September 2016) - Thakur, Pallavi; Chawla, Raman; Goel, Rajeev; Narula, Alka; Arora, Rajesh; Sharma, Rakesh Kumar
Graphical abstract: Highlights: An aquoethanolic extract of stem bark of Berberis aristata (PTRC-2111-A) was characterised using FTIR- and LC–MS analyses. FTIR analysis of PTRC-2111-A revealed the presence of seven characteristic functional groups similar to quercetin. LC–MS analysis revealed the presence of isoquinoline alkaloids as the predominant phytoconstituents, further validated by quantitative alkaloid estimation (ca. 25.44% alkaloids). Bioactivity fingerprinting of PTRC-2111-A revealed its superoxide ion and hydroxyl radical scavenging activities, comparable with the known synthetic standards. PTRC-2111-A exhibited synergistic behaviour with colistin, tigecycline and Augmentin ® against carbapenem-resistant Escherichia coli . Abstract: The aim of this study was to analyse the in vitro synergistic antibacterial potential of an aquoethanolic extract of the stem bark of Berberis aristata (PTRC-2111-A) with third-line antibiotics against carbapenem-resistant Escherichia coli . PTRC-2111-A was prepared and was characterised using phytochemical- and bioactivity-based fingerprinting. Fourier transform infrared spectroscopy (FTIR) and liquid chromatography–mass spectrometry (LC–MS) analyses were performed, and superoxide and hydroxyl scavenging activities were assessed in conjunction with in vitro antimicrobial efficacy testing against the test micro-organism. Analysis of drug combinations of PTRC-2111-A and third-line antibiotics was performed using CompuSyn software. PTRC-2111-A from B. aristata was found to have seven common functional groups in comparison with the pre-identified marker compound quercetin, and phytochemical quantitation analysis revealed the presence of 25.44% alkaloids. Moreover, PTRC-2111-A was found to contain isoquinoline alkaloids, namely berbamine, berberine, reticuline, jatrorrhizine, palmatine and piperazine, as elucidated in the LC–MS analysis. Analysis of combinations of PTRC -2111-A and antibiotics revealed synergistic behaviour [fractional inhibitory concentration index (FICI) < 1] with colistin, tigecycline and amoxicillin/clavulanate potassium (Augmentin ® ), whereas antagonism (FICI > 1) was seen with ertapenem and meropenem.